Relationship between academic procrastination and self-esteem among dental students in Nellore, Andhra Pradesh: A cross-sectional study - M Snehitha; Chandrasekhara Reddy Vuyyuru; R V. S Krishna Kumar; Srinivasulu Gomasani; V Prathyusha (Wolters Kluwer Medknow Publications, 2022)
Background: Procrastination is an extremely prevalent phenomenon and pernicious form of self-regulatory failure. Self-esteem is used to describe peoples' beliefs and feelings about their overall self-worth. Procrastinators have found to carry a heavy cost due to the inability to abide by these values, thereby affecting all domains of life. Purpose: The purpose of this study was to assess the relationship between academic procrastination and self-esteem among dental students in Nellore, Andhra Pradesh. Materials and Methods: A descriptive cross-sectional study was conducted from February to March 2021. The sample consisted of 505 dental students. Data were collected through a questionnaire using the Tuckman Academic Procrastination Scale and Rosenberg Self-esteem Scale. Data collected were analyzed using SPSS software version 14.0. Independent Student's t-test and Pearson's correlation test were performed. P < 0.05 was considered statistically significant. Results: The results indicated that a weak positive correlation (r = 0.02) existed between academic procrastination scores and self-esteem scores. There was a significant difference in mean academic procrastination scores and self-esteem scores among undergraduates and postgraduates. Undergraduates reported higher self-esteem (25.7 ± 1.93) and lower academic procrastination (25.2 ± 1.70) which were found to be statistically significant. Conclusion: The current study found that students who procrastinate more have comparatively lower self-esteem and those with high self-esteem procrastinate less.